2023
DOI: 10.1038/s41598-023-28733-7
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating sea cucumbers as extractive species for benthic bioremediation in mussel farms

Abstract: Filter-feeding mussels blend suspended particles into faeces and pseudo-faeces enhancing organic matter flows between the water column and the bottom, and strengthening benthic-pelagic coupling. Inside operating farms, high bivalve densities in relatively confined areas result in an elevated rate of organic sinking to the seabed, which may cause a localized impact in the immediate surrounding. Deposit-feeding sea cucumbers are potentially optimal candidates to bioremediate mussel organic waste, due to their ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 59 publications
0
8
0
Order By: Relevance
“…Although fish farming is the most widespread in Europe, mussel farming produces more than 1/3 of aquaculture products, making it one of the most important farming practices also in terms of extension (Avdelas et al, 2021). The high extension makes mussel farms particularly suitable for the development of co-culture with sea cucumbers, as the growth of holothurians is strongly affected by high stocking densities under culture conditions (Grosso et al, 2023). Finally, the development of a co-culture between sea cucumbers and P. lividus, the most prized sea urchin in the Mediterranean Sea, could be a valuable solution to reduce the impact of fishing pressures on both organisms, since P. lividus, like sea cucumbers, is now overexploited in several Mediterranean areas (Grosso et al, 2021;Elmasry et al, 2023).…”
Section: Integrated Multitrophic Aquaculturementioning
confidence: 99%
See 1 more Smart Citation
“…Although fish farming is the most widespread in Europe, mussel farming produces more than 1/3 of aquaculture products, making it one of the most important farming practices also in terms of extension (Avdelas et al, 2021). The high extension makes mussel farms particularly suitable for the development of co-culture with sea cucumbers, as the growth of holothurians is strongly affected by high stocking densities under culture conditions (Grosso et al, 2023). Finally, the development of a co-culture between sea cucumbers and P. lividus, the most prized sea urchin in the Mediterranean Sea, could be a valuable solution to reduce the impact of fishing pressures on both organisms, since P. lividus, like sea cucumbers, is now overexploited in several Mediterranean areas (Grosso et al, 2021;Elmasry et al, 2023).…”
Section: Integrated Multitrophic Aquaculturementioning
confidence: 99%
“…According with the literature, the ability of sea cucumbers to survive and grow under IMTA conditions is speciesspecific. H. tubulosa showed high survival rates and positive growth with fish, mussels and sea urchins (Tolon et al, 2017a;Grosso et al, 2021Grosso et al, , 2023, but also showed signs of disease in highly eutrophic conditions, such as those that may occur near fish cages (Sadoul et al, 2022). Similarly, P. tremulus growth rates were enhanced by the addition of salmon sludge to natural sediments, suggesting the suitability of this species to reduce the impact of salmon farming, which is widespread in northern European countries (Sunde and Christophersen, 2023).…”
Section: Integrated Multitrophic Aquaculturementioning
confidence: 99%
“…In this context, deposit-feeding sea cucumbers, important components of the marine benthic biodiversity, are able, thanks to their feeding behavior, to intercept and transform surplus organic matter derived from human activities such as aquaculture 19 , 20 . They are among the most effective seafloor bioturbators, and their digestive system can be considered a real bioreactor where nutrients from ingested organic matter can be quickly assimilated 19 , 21 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Also, these animals can grow faster in mariculture-impacted sites where protein-enriched feed is abundant 25 , 26 . They, indeed, have recently been tested and used as bioremediators in polycultures and Integrated Multi-Trophic Aquaculture (IMTA) systems, with promising results 20 , 27 31 . Despite warm temperatures may negatively affect their metabolic machinery and other functional traits such as, for example, those traits involved in the immune response 32 34 , sea cucumbers are ectothermic and osmo-conformers 35 .…”
Section: Introductionmentioning
confidence: 99%
“…Sea cucumbers have also been proposed recently for embryo toxicity bioassays (Morroni et al, 2020b;Rakaj et al, 2021), showing their suitability as a new test species. Sea cucumbers are an important component of soft benthic communities, which play a key role in controlling organic matter dynamics and detrital pathways in marine sediments (Purcell et al, 2016;Rakaj et al, 2018Rakaj et al, , 2019Grosso et al, 2023;Pensa et al, 2022). However, compared to sea urchins, our knowledge on the sensitivity of sea cucumbers to pollutants and environmental matrices is still in its infancy.…”
Section: Introductionmentioning
confidence: 99%